Infra-estrutura para avaliação e testes de protocolos sociais de comunicação em ambientes tridimencionais compartilhados - Tavares, Tatiana Aires (2004)
The advent of the Internet stimulated the appearance of several services. An example is the communication ones present in the users day-by-day. Services as chat and e-mail reach an increasing number of users. This fact is turning the Net a powerful communication medium. The following work explores the use of communication conventional services into the Net infrastructure. We introduce the concept of communication social protocols applied to a shared virtual environment. We argue that communication tools have to be adapted to the Internet potentialities. To do that, we approach some theories of the Communication area and its applicability in a virtual environment context. We define multi-agent architecture to support the offer of these services, as well as, a software and hardware platform to support the accomplishment of experiments using Mixed Reality. Finally, we present the obtained results, experiments and products